Serum protein levels in primary biliary cirrhosis - MacSween, R. N. M. (1972)
Serum levels of albumin, transferrin, α(2)-macroglobulin, β(1)C/β(1)A, IgA, IgG, and IgM have been determined in 73 patients with primary biliary cirrhosis and in age- and sex-matched controls. A highly significant fall in albumin was demonstrated, and there were highly significant increases in α(2)-macroglobulin and all three immunoglobulin levels. Transferrin and β(1)/Cβ(1)A levels were unchanged. No significant correlations were found between the titre of antimitochondrial antibody, the duration of symptoms, and any of the serum proteins estimated. A highly significant positive correlation was present between serum albumin and transferrin levels in both patient and control groups.